Kantorowskie inspiracje w spektaklu muzyczno-ruchowym Magdaleny Owczarek pt. "Pars pro toto" = Inspirations by Kantor in the "Pars pro toto" musical-choreographic performance of Magdalena Owczarek - Owczarek, Magdalena (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article presents the most important sources of inspiration for the creative process of creating a two-part musical-choreographic performance ?Pars pro toto?, which was created in the Academy of Music in Łódź, in the field of eurhythmics. It was probably the first full-scale author's performance in the history of Polish eurhythmics prepared at the Academy of Music. For students, participating in the process of creating a theater performance is an extraordinary experience, so different from everyday lectures and exercises.
Keywords: Kantor, Tadeusz (1915-1990); minimalizm; walc; interpretacja; inspiracja; spektakl muzyczno-ruchowy; minimalism; waltz; interpretation; inspiration; musical-choreographic performance